Distance education: its organization and management (2001)
Distance education is a means of bringing education to the door step of the people who, otherwise would have not been opportuned to have access to formal education. It thus remove the barriers to formal education and enables a lot of people access to learning while they were still keeping their jobs. But to be effective it must be properly planned, organised implemented and well managed. This paper therefore outlines the process of properly concieving, planning, organising, implementing and managing a result oriented distance learning programme. Since it covers a wider geographical area than the formal education, its planning, organisation and management differ substancially from the organisation and management of a formal education setting